About Innovations in the Approach to the Modernization of Education in Russia and other CIS Countries - S. Polutina; K. Pshenko (Евразийская интеграция: экономика, право, политика)
The article briefly describes the achievements and problems of modernization of education in the member states of the CIS, substantiates the relevance of its further implementation. The authors offer a new look at the approach to modernization and focus their attention on enhancing its system origin. The author characterizes the key objective of this modernization and the main ways to achieve it through the mobilization of all the educational potential of society.